Genome wide analysis of 3′ UTR sequence elements and proteins regulating mRNA stability during maternal-to-zygotic transition in zebrafish - Vejnar, Charles E.; Abdel Messih, Mario; Takacs, Carter M.; Yartseva, Valeria; Oikonomou, Panos; Christiano, Romain; Stoeckius, Marlon; Lau, Stephanie; Lee, Miler T.; Beaudoin, Jean-Denis; Musaev, Damir; Darwich-Codore, Hiba; et al. (Genome Research, 2019)
Posttranscriptional regulation plays a crucial role in shaping gene expression. During the maternal-to-zygotic transition (MZT), thousands of maternal transcripts are regulated. However, how different cis-elements and trans-factors are integrated to determine mRNA stability remains poorly understood. Here, we show that most transcripts are under combinatorial regulation by multiple decay pathways during zebrafish MZT. By using a massively parallel reporter assay, we identified cis-regulatory sequences in the 3′ UTR, including U-rich motifs that are associated with increased mRNA stability. In contrast, miR-430 target sequences, UAUUUAUU AU-rich elements (ARE), CCUC, and CUGC elements emerged as destabilizing motifs, with miR-430 and AREs causing mRNA deadenylation upon genome activation. We identified trans-factors by profiling RNA–protein interactions and found that poly(U)-binding proteins are preferentially associated with 3′ UTR sequences and stabilizing motifs. We show that this activity is antagonized by C-rich motifs and correlated with protein binding. Finally, we integrated these regulatory motifs into a machine learning model that predicts reporter mRNA stability in vivo.
10.1101/gr.245159.118